Effect of Mild and Severe Unilateral Knee Joint Pain on Gait in Elderly Females. (7th December 2014) - Sugiura, Hiroki; Demura, Shinichi
Abstract : Gait change in the elderly may be a strategy to maintain postural stability while walking. However, gait laterality is accompanied by back pain or an increased risk of a fall. This study aimed to examine group-related differences and gait laterality in elderly females with mild or severe unilateral knee pain. Seventy-five elderly females (66–87 years old) were included, which comprised the following groups: 47 with mild unilateral knee pain and 28 with severe unilateral knee pain. They completed a 12 m walk test with maximum effort. Stance time, swing time, and step length were selected as evaluation parameters. A two-way ANOVA (group× leg) was used for analysis. No significant differences were found in interaction or in either main factor of the group and leg. In conclusion, elderly females do not show group-related differences or gait laterality regardless of the degree (mild or severe) of unilateral knee pain.